Resistance of Poligamous Women A Normative Sociological Analysis of Polygamy in Pesantren - Siti Raudhatul Jannah; Mustain Mustain; Yuyun Wahyu Izzati (Budapest International Research and Critics University, 2020)
How do women who are polygamied, especially the wives of a Pesantren leader, play a role of a Kiai wife with the status of the first, the second or the third, even the fourth wife? The researcher interacts with these women using the personal language and informal language of the informants to obtain rich data. As a result, women's resistance to polygamy is increasingly gaining space and place on social media, where each polygamous wife is free to express and articulate her views. On social media, women who are polygamied are free to claim their happiness with their husband without involving other wives of their husband. This proves that a polygamous wife also craves the husband as her own, not to be shared with other wives. This fact is a form of their resistance to the behavior of polygamy of their husbands.